Centralized and local legal regulation of labor relations: problems of correlation and development - V. S. Venediktov; K. Yu. Melnyk (Bulletin of Kharkiv National University of Internal Affairs)
The current state of centralized and local legal regulation of labor relations in Ukraine has been studied and its shortcomings have been identified. The points of view of scientists regarding the essence of centralized and local legal regulation of labor relations have been analyzed.